Role of seafloor production versus continental basalt weathering in Middle to Late Ordovician seawater 87Sr/86Sr and climate - Avila, Teresa D.; Saltzman, Matthew R.; Adiatma, Y. Datu; Joachimski, Michael; Griffith, Elizabeth M.; Olesik, John W. (Earth and Planetary Science Letters, 2022)
The global climate of the Ordovician Period (486.9 to 443.1 Ma) is characterized by cooling that culminated in the Hirnantian glaciation. Chemical weathering of Ca- and Mg-bearing silicate minerals and the subsequent trapping of carbon in marine carbonates act as a sink for atmospheric CO2 on multi-million-year time scales, with basaltic rocks consuming CO2 at a greater rate than rocks of granitic composition. The oceanic Sr isotope ratio (87Sr/86Sr) can act as a geochemical proxy for the relative proportion of basaltic versus granitic weathering. Oxygen isotopes (O) act as a proxy for paleotemperature and ice volume, providing a useful complement to 87Sr/86Sr in studies of ancient climate. Previous studies have reported stepwise cooling (increasing O) during the Middle to Late Ordovician. Combined with Sr and C cycle models, this has led to the hypothesis that continental silicate weathering of mafic material drove Ordovician cooling (e.g., the Taconic Orogeny). However, Sr and C cycle models have not accounted for an apparent rise in sea level and seafloor production in the Middle Ordovician (Darriwilian), which would increase the hydrothermal Sr flux as well as degassing along continental volcanic arcs. Furthermore, some Ordovician studies contain temporal uncertainty between 87Sr/86Sr and O curves if they are not based on paired analyses, which can obscure the relationship between silicate weathering and cooling. Here, we present new paired 87Sr/86Sr and O data from conodont apatite and integrate this with both a deterministic (forward) and stochastic (reverse) modeling approach to argue that increased hydrothermal weathering played a role in driving marine 87Sr/86Sr, specifically an inflection occurring in the Pygoda serra conodont zone of the mid-Darriwilian Stage (∼ 460.9 Ma ± 1 My). This 87Sr/86Sr inflection is accompanied by an increase in O, consistent with climate cooling. Clarifying the role of seafloor production for marine 87Sr/86Sr and the implications for Ordovician cooling allows for a more nuanced understanding of the factors that drive multi-million-year<br
Keywords: Ordovician; geochemistry; paleoclimatology; silicate weathering; conodont; strontium